PNPLA3(I148M) inhibits lipolysis by perilipin-5-dependent competition with ATGL - Witzel, Hagen Roland; Schwittai, Inga Maria Gertrud; Hartmann, Nils; Mueller, Sebastian; Schattenberg, Jörn Markus; Gong, Xue-Min; Backs, Johannes; Schirmacher, Peter; Schuppan, Detlef; Roth, Wilfried; Straub, Beate Katharina (Cells, 2023)
The single nucleotide polymorphism I148M of the lipase patatin-like phospholipase domain containing 3 (PNPLA3) is associated with an unfavorable prognosis in alcoholic and non-alcoholic steatohepatitis (ASH, NASH), with progression to liver cirrhosis and development of hepatocellular carcinoma. In this study, we investigated the mechanistic interaction of PNPLA3 with lipid droplet (LD)-associated proteins of the perilipin family, which serve as gatekeepers for LD degradation.
Online veröffentlicht am 24. Dezember 2022
Gesehen am 21.02.2023